2010
DOI: 10.1016/j.bcp.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of anti-apoptotic Bcl-2 family members Mcl-1, Bcl-2, and Bcl-xL on Celecoxib-induced apoptosis

Abstract: Please cite this article as: Rudner J, Elsaesser SJ, Müller A-C, Belka C, Jendrossek V, Differential effects of anti-apoptotic Bcl-2 family members Mcl-1, Bcl-2, and Bcl-xL on Celecoxib-induced apoptosis, Biochemical Pharmacology (2008Pharmacology ( ), doi:10.1016Pharmacology ( /j.bcp.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…In this regard, Bax-deficient Jurkat cells seem to be entirely dependent on Mcl-1 (20,40,41). The prominent inhibitory action of Bcl-xL and the downregulation of Mcl-1 during DHA-induced apoptosis fit well into the concept that proapoptotic Bak is kept in check by Mcl-1 and Bcl-xL and that apoptosis execution requires abrogation of the inhibitory action of these antiapoptotic Bcl-2 family members (42,43).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In this regard, Bax-deficient Jurkat cells seem to be entirely dependent on Mcl-1 (20,40,41). The prominent inhibitory action of Bcl-xL and the downregulation of Mcl-1 during DHA-induced apoptosis fit well into the concept that proapoptotic Bak is kept in check by Mcl-1 and Bcl-xL and that apoptosis execution requires abrogation of the inhibitory action of these antiapoptotic Bcl-2 family members (42,43).…”
Section: Discussionmentioning
confidence: 69%
“…Because RNAimediated downregulation of NOXA inhibited DHAinduced apoptosis to some extent, a role of NOXA in DHA-mediated apoptosis can be assumed. This is reminiscent of the role of NOXA and Mcl-1 in the cellular response to the nonsteroidal anti-inflammatory drug celecoxib, histone deacetylase inhibitors, and proteasome inhibitors (20,45). Although the observations that loss of Bak and pretreatment with zVAD-fmk do not prevent the upregulation of NOXA suggest that NOXA upregulation is an upstream event, the exact role of NOXA in DHA-induced apoptosis remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, a great deal of effort has been focused on the development of agents that target and inhibit COX-2 activity for use in cancer chemotherapy. Unfortunately, moderate or high therapeutic doses of selective COX-2 inhibitors lead to a variety of gastrointestinal and cardiovascular toxicities, and these adverse effects have greatly limited their clinical use in cancer chemoprevention and treatment [5,6]. Recent studies have shown that combined treatment of NSAIDs with other anticancer agents, such as γ-tocotrienol, resulted in synergistic antiproliferative effects [7].…”
Section: Introductionmentioning
confidence: 98%